The Historicity of Muhammadiyah: The Idea of Founding Muhammadiyah - Literature Analysis - Khozin, Khozin; Lasaksi, Pardin (Westscience Press, 2024)
This research explores the historicity of Muhammadiyah, exploring the ideas of its founding, its historical context, and its impact on Indonesian society. Through a systematic literature review and thematic analysis, this research reveals the basic ideas articulated by Ahmad Dahlan, the founder of Muhammadiyah, by highlighting the theological principles of tajdid and ijtihad. The historical context section examines the emergence of this movement in the socio-political landscape of the early 20th century in Indonesia, emphasizing the impact of Dutch colonial rule and its relationship with global Islamic reformist movements. This research then assesses Muhammadiyah's impact on Indonesian society, including education, social welfare initiatives, and its broader influence in shaping modern Indonesian Islam. Thematic analysis of scientific works shows Muhammadiyah's role in providing holistic education, encouraging intellectual independence, and overcoming social challenges through social welfare programs. The influence of this movement in shaping progressive interpretations of Islam in cultural and societal discourse is also explored. The synthesis of findings underscores the interconnected nature of Muhammadiyah's basic ideas, historical context, and social impact. This movement emerged as a transformative force, dynamically responding to local and global challenges while remaining rooted in its basic principles. This research contributes to scholarly understanding of Islamic reform movements and provides insight into the complex interactions between theological ideals and societal transformation.